Social capital and cost of debt in Vietnamese household businesses - Phuoc Vu Ha; Hong Hanh Huynh (Cogent Business & Management, 2022)
The paper provides the impact of social capital on the cost of debt of rural household businesses in Vietnam by using the panel data sample of 4,874 household businesses. Social capital is considered as the connections with people in the society including connections with people in the same business sector, people in the different business sector, bank officials and politicians. Besides, social capital is also measured as the assistance from government, state-owned commercial banks, state-owned enterprises, private commercial banks, friends & relatives and business association. The results show that the connections with politicians, the assistance from government, state-owned enterprises, private commercial banks, friends & relatives and business associations can help the household businesses in reducing the cost of using debts. The paper draws up a broader picture about the use of informal resources like social capital in household businesses. Accordingly, this highlights the importance of social capital in a network-oriented country like Vietnam.
Keywords: H31; J24; L14; L25; O53; 650; household; household businesses; social capital; social networks